2005
DOI: 10.1358/mf.2005.27.5.908643
|View full text |Cite
|
Sign up to set email alerts
|

Research on adverse drug events. I. Muscarinic M3 receptor binding affinity could predict the risk of antipsychotics to induce type 2 diabetes

Abstract: Antipsychotics are associated with a wide range of adverse effects, several of which may represent a serious health risk to patients. There is an increased concern about metabolic disturbances associated with antipsychotics, including weight gain, dyslipidemia, hyperglycemia, and type 2 diabetes. However, little is known about the mechanisms underlying antipsychotic-induced metabolic disturbances and, in particular, those related to the induction of abnormal glucose metabolism and diabetes. The present article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 0 publications
8
77
0
1
Order By: Relevance
“…Our findings have recently been confirmed in other studies (Silvestre and Prous, 2005), and in H 1 receptor knockout mice the mechanism has been traced to H 1 -mediated hypothalamic AMP kinase activation (Kim et al, 2007). Quetiapine is a histamine H 1 receptor antagonist with a K i of 11 nM, which induces weight gain (Allison et al, 1999) and has pronounced sedative effects (Cohrs et al, 2004;Thase et al, 2006).…”
Section: Critical Off-target Activitiessupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings have recently been confirmed in other studies (Silvestre and Prous, 2005), and in H 1 receptor knockout mice the mechanism has been traced to H 1 -mediated hypothalamic AMP kinase activation (Kim et al, 2007). Quetiapine is a histamine H 1 receptor antagonist with a K i of 11 nM, which induces weight gain (Allison et al, 1999) and has pronounced sedative effects (Cohrs et al, 2004;Thase et al, 2006).…”
Section: Critical Off-target Activitiessupporting
confidence: 82%
“…The quetiapine metabolite has a 20-to 80-fold increased affinity for M 1 , M 3 , and M 5 receptors compared to its parent compound. This metabolic activation is of potential clinical significance as M 3 antagonism has been postulated as a contributing factor for antipsychotic-induced diabetes and hyperglycemia (Johnson et al, 2005;Silvestre and Prous, 2005). Moreover, antimuscarinic activity is commonly associated with side effects, such as dry mouth, mydriasis, increased intraocular pressure, urinary retention, and hyperthermia.…”
Section: Critical Off-target Activitiesmentioning
confidence: 99%
“…In accordance with this view, mice with targeted deletions in the M 3 gene have reduced basal levels of insulin and glucagons. 88 Johnson et al 89 also found that low concentrations of olanzapine and clozapine (but not risperidone or ziprasidone) can markedly and selectively impair cholinergicstimulated insulin secretion by blocking muscarinic M 3 receptors in isolated rat islet cells. In vitro binding and functional data also showed that olanzapine and clozapine, unlike the other two atypical agents or haloperidol, are potent muscarinic M 3 antagonists.…”
Section: Diabetes 62mentioning
confidence: 99%
“…A meta-analysis by MatsuiSakata et al 53 indicated that disruption of H 1 function may interfere with leptin-mediated appetite suppression, an effect that could lead to weight gain and insulin resistance. Moreover, Silvestre and Prous 88 found that antipsychotic drug affinity for muscarinic M 3 receptors is a significant predictor of the development of diabetes. This finding is supported by the fact that M 3 is highly expressed by pancreatic b-cells, where it is thought to play a central role in regulating glucose-dependent acetylcholine modulation of insulin secretion.…”
Section: Diabetes 62mentioning
confidence: 99%
See 1 more Smart Citation